2023
DOI: 10.3390/en16093930
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Fast but Reliable Energy Performance Evaluation Method for Existing Residential Building Stock

Stefano Converso,
Paolo Civiero,
Stefano Ciprigno
et al.

Abstract: Building a reliable energy model for old residential buildings with insufficient documentation and user assistance is a challenging and time-consuming task. Nevertheless, the ambitious European decarbonization targets require this building stock to be renovated, making energy assessment a key priority. In line with this goal, the following study explores a more simplified and automatic framework to generate a residential building energy model (BEM). The paper’s approach is based on the concept of urban buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In line with this goal, BIM may play a crucial role. Converso et al [103] showed the benefits of BIM in energy models. They carried out a study using Google Maps and various BIM-based programs to remodel three residential buildings with different climatic conditions and construction periods, resulting in the creation of a building energy model (BEM).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this goal, BIM may play a crucial role. Converso et al [103] showed the benefits of BIM in energy models. They carried out a study using Google Maps and various BIM-based programs to remodel three residential buildings with different climatic conditions and construction periods, resulting in the creation of a building energy model (BEM).…”
Section: Discussionmentioning
confidence: 99%